The rise and fall of Europe's new stock markets - Giudici, Giancarlo; Roosenboom, Peter (Emerald, 2004)
The advent of new stock markets (the German Neuer Markt, the French Nouveau Marche, the Italian Nuovo Mercato and Nasdaq Europe) has been one of the most important reforms of stock exchanges in Continental Europe in the 1990s. These stock markets aimed at attracting early stage, innovative and high-growth firms that would not have been viable candidates for public equity financing on the main markets of European stock exchanges. Of these new markets, the Neuer Markt emerged as Europe's answer to NASDAQ. However, Europe's new stock markets met with only limited success. Stock prices plummeted after the ending of the stock market bubble and new markets suffered from poor liquidity, insider trading scandals and accounting frauds. This volume provides an overview of the rise and fall of Europe's new stock markets. It contains twelve papers which investigate the characteristics, the ownership structure and the market performance of companies in the short and long run. In addition this volume examines the role of venture capitalists. New stock markets offered venture capitalists an attractive exit for their investments and helped to create a more vibrant venture capital industry in Europe. The private equity market in Europe today is as large as it was just before the advent of new stock markets. As such, the need for stock markets that allow private equity investors to divest their equity stakes in growth companies continues to exist.
Keywords: Stock exchanges -- Europe.; elektronické knihy; electronic books